2022
DOI: 10.3390/vetsci9120684
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile of Foeniculum vulgare Subsp. piperitum Essential Oils and Evaluation of Acaricidal Efficacy against Varroa destructor in Apis mellifera by In Vitro and Semi-Field Fumigation Tests

Abstract: Varroatosis is an important parasitic disease of Apis mellifera caused by the mite Varroa destructor (V. destructor). The parasite is able to transmit numerous pathogens to honeybees which can lead to colony collapse. In recent years, the effectiveness of authorized drug products has decreased due to increasing resistance phenomena. Therefore, the search for alternatives to commercially available drugs is mandatory. In this context, essential oils (EOs) prove to be a promising choice to be studied for their kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…The extreme pharmacological practicality of EOs when administered by fumigation techniques was also demonstrated by Bava et al (2022) [137]. The authors found that fennel EO vapors were toxic to Varroa, while bees began to experience toxic effects only when subjected to doses ten times higher than those of Varroa [137]. Regarding this, it is also important to cite the study conducted by Hoppe (1990) [138].…”
Section: Application Methods In Laboratory and Field Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…The extreme pharmacological practicality of EOs when administered by fumigation techniques was also demonstrated by Bava et al (2022) [137]. The authors found that fennel EO vapors were toxic to Varroa, while bees began to experience toxic effects only when subjected to doses ten times higher than those of Varroa [137]. Regarding this, it is also important to cite the study conducted by Hoppe (1990) [138].…”
Section: Application Methods In Laboratory and Field Studiesmentioning
confidence: 86%
“…The effectiveness and low risk to honeybees of fumigation as an administration technique for Acantholippia seriphioides and Schinus molle EOs to control V. destructor in a laboratory setting (16% and 8% mortality rate for honeybees, respectively, for Acantholippia seriphioides and Schinus molle), compared to the use of the complete exposure method (87% and 42% mortality rate for honeybees, respectively), has been proven [136]. The extreme pharmacological practicality of EOs when administered by fumigation techniques was also demonstrated by Bava et al (2022) [137]. The authors found that fennel EO vapors were toxic to Varroa, while bees began to experience toxic effects only when subjected to doses ten times higher than those of Varroa [137].…”
Section: Application Methods In Laboratory and Field Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this evidence, veterinarians or beekeeping technicians should recommend the application of GBPs. For example, the treatments should be administered in combination with bio-techniques, such as queen caging, and the use of drugs that are unlikely to lead to the development of resistance, such as those based on essential oils, should be preferred [ 18 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being composed of several molecules that have different cellular targets, treated pest populations are unlikely to develop drug resistance [ 38 ]. Moreover, being natural compounds, they are easily degradable in the environment and do not accumulate in the food matrices of the hive [ 39 , 40 , 41 ]. EOs from the Lamiaceae family have proven to be particularly effective in controlling V. destructor [ 33 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%